2014
DOI: 10.1038/ncomms6081
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-proteasome system controls ciliogenesis at the initial step of axoneme extension

Abstract: Primary cilia are microtubule-based sensory organelles that organize numerous key signals during developments and tissue homeostasis. Ciliary microtubule doublet, named axoneme, is grown directly from the distal end of mother centrioles through a multistep process upon cell cycle exit; however, the instructive signals that initiate these events are poorly understood. Here we show that ubiquitin-proteasome machinery removes trichoplein, a negative regulator of ciliogenesis, from mother centrioles and thereby ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
168
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(174 citation statements)
references
References 51 publications
6
168
0
Order By: Relevance
“…UBR5 was identified in a whole-genome shRNA screen as a positive regulator of ciliogenesis (90), with UBR5 depletion causing decreased primary cilia formation. This screening hit was not further validated and the mechanism underlying this effect is yet to be determined, but the UPS is an established regulator of ciliogenesis (91).…”
Section: Emerging Functional Roles For Ubr5mentioning
confidence: 99%
“…UBR5 was identified in a whole-genome shRNA screen as a positive regulator of ciliogenesis (90), with UBR5 depletion causing decreased primary cilia formation. This screening hit was not further validated and the mechanism underlying this effect is yet to be determined, but the UPS is an established regulator of ciliogenesis (91).…”
Section: Emerging Functional Roles For Ubr5mentioning
confidence: 99%
“…Despite its name, KCTD17 has been shown to act as a substrate-adaptor for Cul3-RING ubiquitin ligases (CRL3s) to regulate proteosomal degradation of specific targets. 22, 36, 37 We observed that hepatic Kctd17 expression is robustly increased in HFD-fed and db/db mice (Figure 4A). Next, we confirmed our LC-MS/MS results by immunoprecipitation of endogenous KCTD17 in livers from HFD-fed mice with anti-PHLPP2 antibody, and vice versa (Figure 4B).…”
Section: Resultsmentioning
confidence: 89%
“…To understand the endogenous regulatory machinery that mediates PHLPP2 degradation in obese liver, we performed sequential LC/MS-MS-based screens, which identified novel glucagon/PKA-mediated PHLPP2 phosphorylation at Ser1119 and Ser1210, which augments PHLPP2 interaction with KCTD17, an adaptor protein for Cul3-RING ubiquitin ligases. 22 Interestingly, KCTD17 expression is increased in livers from obese mice and patients with NASH, linking glucagon-induced PHLPP2 phosphorylation with degradation. Thus, knockdown of KCTD17 in obese mice increases endogenous PHLPP2 and ameliorates obesity-induced fatty liver, revealing a novel strategy in the treatment of obesity-mediated NAFLD/NASH.…”
Section: Introductionmentioning
confidence: 99%
“…Given the results, we focused on the mechanisms by which cell cycle cues control ciliogenesis in the current study. Recent reports noted that proteolysis of ciliary proteins including Trichoplein contributes cell cycle exit and cilia formation (Tang et al 2013;Kasahara et al 2014). Therefore, it is conceivable that the defective formation of the cilia caused by the depletion of mRNA splicing regulators is due to deregulation of the cell cycle exit.…”
Section: Introductionmentioning
confidence: 99%